Effect of a novel temperature‐controlled laminar airflow device on personal breathing zone aeroallergen exposure. (10th June 2014) - Gore, R. B.; Boyle, R. J.; Gore, C.; Custovic, A.; Hanna, H.; Svensson, P.; Warner, J. O.
Abstract Temperature‐controlled laminar airflow improves symptoms in atopic asthmatics, but its effects on personal allergen exposure are unknown. We aimed to evaluate its effects on personal cat allergen and particulate exposures in a simulated bedroom environment. Five healthy volunteers lay under an active and an inactive temperature‐controlled laminar airflow device for 175 min, in a simulated bedroom containing bedding from a cat owner. Total airborne particles (≥0.5 – ≥10 μm diameter) were quantified with a laser particle counter. Airborne allergen was sampled with Institute of Occupational Medicine filters. Inhaled exposure was sampled with nasal air samplers. Allergen‐containing particles were quantified by immunoassay. Treatment reduced total airborne particles (>0.5 μm diameter) by >99% (P < 0.001) and reduced airborne allergen concentration within the breathing zone (ratio of median counts = 30, P = 0.043). Treatment reduced inhaled allergen (ratio of median counts = 7, P = 0.043). Treatment was not associated with a change in airborne allergen concentration outside of the breathing zone (P = 0.160). Temperature‐controlled laminar airflow treatment of individuals in an allergen‐rich experimental environment results in significant reductions in breathing zone allergenic and non‐allergenic particle exposure, and in inhaled cat allergen exposure. These findings may explain the clinical benefits of temperature‐controlled laminar airflow.